Utilization of Forest Plants as Local Food Sources for the Oben Village Community, Nekamese District, Kupang Regency - Nur Aini Bunyani; Maya Roman; Jorita Naisanu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
Forest plants as a source of food as a substitute for carbohydrates have long been used by the village community. Forest plants directly address the food insecurity experienced by villagers. This research was conducted in Oben Village, Nekamese District, Kupang Regency on April 24 to July 22, 2018. The aim of this study was to describe the use of forest plant species as a local food source and their traditional processing by the Oben Village Community, Nekam District, Kupang Regency. These are the exploration, exploration and interview methods. The data obtained were analyzed descriptively. The results of this study were: Found 5 types of forest tubers that are commonly used by the people of Oben Village as a food source, namely Dioscorea alata L; Dioscorea esculenta L; Dioscorea hispida D; Dioscorea pentaphylla and Amorphophallus compulatus, The traditional way of processing forest tubers is that they can be washed immediately, then roasted, boiled or steamed, processed into local chips, compote and flour as cake ingredients.